2005
DOI: 10.1016/j.pain.2005.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor mediates hyperalgesia and cachexia in auto-immune arthritis

Abstract: Pain and cachexia are two of the most debilitating aspects of rheumatoid arthritis. Despite that, the mechanisms by which they are mediated are not well understood. We provide evidence that nerve growth factor (NGF), a secreted regulatory protein that controls neuronal survival during development, is a key mediator of pain and weight loss in auto-immune arthritis. Function blocking antibodies to NGF completely reverse established pain in rats with fully developed arthritis despite continuing joint destruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 55 publications
6
91
0
Order By: Relevance
“…βNGF binds and activates its cognate receptor, tropomyosin-related kinase A receptor (TrkA), up-regulating the expression and activity of pathways that enhance acute and chronic pain. Antagonism of the βNGF/TrkA signaling pathway has been shown in animal and clinical studies to be a potent means of attenuating pain sensation in a number of clinical indications (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…βNGF binds and activates its cognate receptor, tropomyosin-related kinase A receptor (TrkA), up-regulating the expression and activity of pathways that enhance acute and chronic pain. Antagonism of the βNGF/TrkA signaling pathway has been shown in animal and clinical studies to be a potent means of attenuating pain sensation in a number of clinical indications (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Anti-NGF antibody injected 6 h after LC completely blocked DOMS. Since the bradykinin released during exercise had already initiated the DOMS process 6 h after LC and the biological half-life of the antibody is reported to be several days (Shelton et al, 2005), NGF antibody might have continuously reversed DOMS rather than suppressing initiation of the processes that led to DOMS. Only 10 g of anti-NGF antibody was needed to suppress DOMS with an early injection (at 6 h after LC), but 30 g was needed with later injection (10 g was ineffective) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NGF has also been implicated as a mediator of weight loss (26). Progressive unintentional weight loss, also known as cachexia, can be a clinical consequence of a chronic systemic inflammation, such as RA (42).…”
Section: Suppression Of Weight Loss In Ciamentioning
confidence: 99%
“…Recognition of NGF as a mediator of pain and its involvement in persistent pain in adults has stimulated the development of numerous biologics and pharmaceuticals that antagonize its activity (5,11). Neutralization of NGF by specific Abs has been shown to decrease thermal and mechanical hyperalgesia in animal models of acute and chronic pain that include: cutaneous injection of CFA (17,25), arthritis-associated pain (26), and bone cancer (27). A phase II clinical trial with the anti-NGF mAb tanezumab demonstrated suppression of osteoarthritic pain (28).…”
mentioning
confidence: 99%